KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP ILIR TIMUR KOTA PALEMBANG - Fahmi, Muhammad; Hari, Kurnia Krisna (Balance : Jurnal Akuntansi dan Bisnis, 2023)
The purpose of this research was to determine the influence of service quality and tax sanctions on individual taxpayer compliance. The type of research used is associative research. The place of research was carried out at the Pratama Ilir Timur Tax Service Office, Palembang City. The data used is primary data. The data collection method used in this research is a questionnaire. The data analysis techniques used in this research are validity test, reliability test, classical assumption test, coefficient of determination, multiple linear regression analysis, and t test assisted by the Statistical Program for Special Science (SPSS). The research results show that Service Quality has no effect on individual taxpayer compliance, while tax sanctions have an effect on individual taxpayer compliance.